PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIA 2 SMA BABUSSALAM PEKANBARU - Dela Fauziah; Titi solfitri; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the results of daily test scores obtained from mathematics subject teachers on mathematics induction material for semester 2019/2020 shows that 14 out of 25 students in class XI MIA 2 Babussalam Pekanbaru High School scored under KKM which is 70 and the learning process is still dominated by teachers. The learning process is seen as one of the main factors influencing learning outcome so this research aims to improve the learning process and improve mathematics learning outcomes through the application of the Problem Based Learning model. This research is a classroom action research with two cycles. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Activity Sheets) and data collecting instruments (Observation Sheets and Students Mathematic Tests). Data collection techniques in this research used are observation techniques and test techniques. The observation sheets were analyzed in qualitative desciptive, while the students Mathematic tests were analyzed in quantitative descriptive. Based on the analysis of students and teacher activities after implementation of the Problem Based Learning model, it can be concluded that there is an improvement of learning process. In quantitative analysis, On knowledge competence the percentage of students who can reach KKM on a basic score of 11 students or 44% increased to 15 students or 60% in Cycle I and increased to 17 students or 68% in Cycle II. On skill competence, the percentage of students who can reach KKM on a cycle I score of 12 students or 48% increased to17 students or 68% in Cycle II. Based on the result, it can be concluded that the implementation of Problem Based Learning model can improve the learning process and the students’ mathematics learning outcomes in class of XI MIA 2 SMA Babussalam Pekanbaru. Key Words: Mathematics Learning Achievement, Problem Based Learning Model, Classroom Action Researc